Parents' Knowledge Overview of the Implementation of Toilet Training for Children Aged 4-5 Years (at Arifah Kindergarten, Lassang Barat Village, North Polombangkeng District, Takalar Regency) - Kasmawati K; Sartika S; Nur Rahmi (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Toilet training is an effort to train children to develop the habit of controlling urination and defecation activities in the right and regular place. In addition, toilet training also teaches children to clean up their own waste and put their pants back on independently without the help of others. A child's readiness for toilet training can be influenced by parental motivation, the child's physical, psychological, and intellectual readiness. The purpose of this study is to understand the parents' knowledge overview of the implementation of toilet training for children aged 4-5 years at Arifah Kindergarten, Lassang Barat Village, North Polombangkeng District, Takalar Regency. The research method used is descriptive observational with a survey method. The research was conducted using a questionnaire along with a respondent consent form. The results of the study conducted on 30 parents as respondents at Arifah Kindergarten, Lassang Barat Village, North Polombangkeng District, Takalar Regency, showed that most respondents had good knowledge about the implementation of toilet training for children aged 4-5 years, amounting to 66.7%. Meanwhile, 23.3% had sufficient knowledge, and 10% had less knowledge about the implementation of toilet training for children aged 4-5 years. It is expected that future researchers will continue this study by developing additional variables from this research